The impact of biological and cultural racisms on attitudes towards immigrants and immigration public policies - Ramos, Alice (2019)
Based on ESS-7 data, this paper focuses on two attitudinal dimensions about public policies related to immigration: how many can come and who can come. In this context, the hypothesis concerning the bi-dimensionality of racism was supported and, as predicted, biological racism is more antinormative than cultural racism. Both biological and cultural racism predict opposition to immigration and adhesion to ethnicist criteria on the selection of immigrants. As hypothesised, the relationship between racism and opposition to immigration and adhesion to ethnicist criteria is mediated by threat perceptions. Specifically, symbolic and realistic threats mediate the effect of biological and cultural racism on opposition to immigration and on ethnicist criteria. The hypothesis that the mediation effects are moderated by the country’s quality of democracy was supported, indicating that the mediation effects are stronger in countries with a higher quality of democracy. Results are discussed within the context of racism theories as a bi-dimensional concept and in the framework of the role of legitimation processes in social discrimination.